DIGITALIZATION OF THE ECONOMY: CONCEPTS, PROBLEMS AND IMPLEMENTATION STRATEGY - Mr. Azamat Davletyarov; Dr. Dilmurod Suyunov; Dr. Aman T. Kenjabaev (Journals Park Publishing, 2023)
This article analyzes the concept of the digital economy. The concept of regional digital economy is formulated. The essence of the scenario of digital transformation of the market is investigated. In particular, the problems of production and business of the regional economy are disclosed, some key terms and expressions are clarified from the standpoint of the research topic.
Keywords: digital economy, regional digital economy, digital platform, digital transformation of the market, innovative business models of IT Park, IT certificate.